The Role of Advanced Penetration Testing Techniques in Enhancing Cybersecurity: A Survey on Web Application Security - EMMANUEL BUGINGO; Voltaire ISHIMWE; Ghislaine UWASE SIMBI; Adeline DUSENGE; Jean Baptiste NIZEYIMANA (JUTI: Jurnal Ilmiah Teknologi Informasi, 2026)
The Internet continues to grow as an exciting platform for numerous web applications, providing crucial services to various industries and user communities. However, this expansion comes with an increase in cybersecurity threats, as web applications continue to be a primary target for malicious entities. Despite the creation of numerous security frameworks, yearly reports and the OWASP (Open Web Application Security Project) Top 10 consistently highlight the ongoing presence of severe vulnerabilities in contemporary web platforms. This paper examines the significance of advanced penetration testing methods in enhancing cybersecurity, particularly in the context of web application security. Utilizing a combination of manual and automated testing approaches, incorporating tools such as BURP SUITE and METASPLOIT, this study examines how sophisticated penetration testing can uncover, exploit, and address vulnerabilities, including SQL injections, cross-site scripting (XSS), and weak authentication methods. The results highlight that even small vulnerabilities can have significant practical impacts, emphasizing the importance of ongoing, intelligent testing approaches.